Measuring bank stability: a comparative analysis between Islamic and conventional banks in Malaysia - Abdul Karim, Norzitah; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina; Haron, Razali (Springer, 2018)
The present study provides new empirical evidence of bank stability measures for 50 banks in Malaysia, for a period from 1999 to 2015. There are two methods of measuring bank stability that is using Z-score and CAMELS variables. After calculating, these variables are ranked, with the highest average is ranked as one, and the lowest average is ranked last, or fifty. This is following the method by (Roman and Procedia Economics and Finance, 6(13), 703–712 Roman and Şargu 2013) and (Procedia—Social and Behavioral Sciences, 24, 1530–1545 Dincer et al. 2011) and extending it by introducing the average of total ranking for all variables. The empirical findings suggest that both local Islamic and conventional banks are ranked favourable in overall average bank stability score, sensitivity to market risk, asset quality, earning and profitability, but local conventional banks are recorded favourable ranking in liquidity. Comparing the two types of local banks, conventional banks are ranked better in liquidity, sensitivity to market risk and earning and profitability.